ONLINE LEARNING ASSISTANCE FOR SETIA BHAKTI CATHOLIC HIGH SCHOOL STUDENTS AT THE COVID 19 PANDEMIC PERIOD - Ans Prawati Yuliantari (Randang Tana - Jurnal Pengabdian Masyarakat, 2021)
This article aims to explain the educational program carried out by lecturers and students of the Indonesian Language and Literature Education Program, Universitas Katolik Indonesia Santu Paulus Ruteng, to students at high schools in Manggarai Regency, East Nusa Tenggara Province. The method of implementing the program consists of four stages, namely debriefing students and supervisors of this program, observation of the problems of prospective students, third, based on the results of observations, the supervisor directing students in providing assistance, and fourth is the implementation of mentoring carried out during two weeks. Based on the process that has been carried out, it can be seen that this program can help students at Setia Bhakti high school level to deepen understanding of learning materials they got at school. This system can also replace the role of parents in supervise their children during the online learning process because not every parent has the adequate ability to understand subjects in high school. Meanwhile, the results of the evaluation after the implementation of the program showed that the students wanted similar programs to be continued in the future if face-to-face learning could not be implemented. In addition, the mentoring method can be further refined according to input and feedback from teachers and teachers in partner schools